Clustering of lifestyle behaviors and adiposity in early adolescents in Spain: findings from the SI! Program for Secondary Schools - Patricia Bodega; Gloria Santos-Beneit; Amaya de Cos-Gandoy; Luis A. Moreno; Mercedes de Miguel; Xavier Orrit; Anna Tresserra-Rimbau; Jesús Martínez-Gómez; Sonia L. Ramírez-Garza; Emily P. Laveriano-Santos; Camila Arancibia-Riveros; Ramón Estruch; et al. (BMC, 2023)
Abstract Background Several unhealthy lifestyle behaviors in adolescence are often linked to overweight/obesity. Some of them may be present simultaneously, leading to combined effects on health. Therefore, the clustering of several unhealthy behaviors in adolescents might be associated with adiposity excess. Purpose To identify lifestyle patterns and analyze their association with adiposity in early adolescents. Methods A cross-sectional cluster analysis was performed in 1183 adolescents (50.5% girls) with a mean age of 12.5 (0.4) years included in the SI! Program for Secondary Schools in Spain to identify lifestyle patterns based on healthy diet, step counts, sleep time, and leisure screen time. Generalized mixed models were applied to estimate the association between lifestyle patterns and adiposity indices. Results Four lifestyle patterns were derived: Cluster 1-higher screen time and poorer diet (n = 213), Cluster 2-lower activity and longer sleepers (n = 388), Cluster 3-active and shorter sleepers (n = 280), and Cluster 4-healthiest (n = 302). Except for the number of steps (12,008 (2357) day), the lifestyle behaviors in our sample presented levels far below the recommendations, especially for sleep duration. Cluster 4 included the largest proportion of adolescents from high socioeconomic status families (47.7%) and the lowest prevalence of overweight/obesity (23.1%). Compared to Cluster 4-healthiest, adolescents in the remaining clusters presented a higher prevalence of overweight/obesity and central obesity, showing Cluster 3 the highest prevalences (PR:1.31 [95%CI: 1.31, 1.31] and PR:1.40 [95%CI: 1.33, 1.47]). Conclusions Clustering of lifestyle patterns in early adolescence allows the identification of individuals with excess adiposity, in whom health promotion strategies should be stressed, especially in socioeconomically disadvantaged groups. Trial registration Clinical Trial Registry, NCT03504059. Registered 20/04/2018-Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03504059 .